Consensus statement from the International Radiosurgery Oncology Consortium for Kidney for primary renal cell carcinoma. (March 2016) - Siva, Shankar; Ellis, Rodney J; Ponsky, Lee; Teh, Bin S; Mahadevan, Anand; Muacevic, Alexander; Staehler, Michael; Onishi, Hiroshi; Wersall, Peter; Nomiya, Takuma; Lo, Simon S
Aim: To provide a multi-institutional consensus document for stereotactic body radiotherapy of primary renal cell carcinoma.Materials & methods: Eight international institutions completed a 65-item survey covering patient selection, planning/treatment aspects and response evaluation.Results: All centers treat patients with pre-existing hypertension and solitary kidneys. Five institutions apply size constraints of 5–8 cm. The total planning target volume expansion is 3–10 mm. All institutions perform pretreatment imaging verification, while seven institutions perform some form of intrafractional monitoring. Number of fractions used are 1–12 to a total dose of 25 Gy–80 GyE. Imaging follow-up for local tumor response includes computed tomography (n = 8), PET-computed tomography (n = 1) and MRI (n = 5). Follow-up frequency is 3–6 months for the first 2 years and 3–12 months for subsequent 3 years.Conclusion: Key methods for safe implementation and practice for stereotactic body radiotherapy kidney have been identified and may aid standardization of treatment delivery.